ROLE OF VITAMIN D IN THE EFFICIENCY OF ANTIRESORPTIVE THERAPY - N V Toroptsova (Современная ревматология, 2009)
Vitamin D deficiency is one of the substantiated risk factors of osteoporosis. This vitamin is required to provide intestinal calcium absorption, bone metabolism regulation, and neuromuscular functions in the body. Vitamin D deficiency results in increased bone metabolism, causing bone loss progression and increasing the risk of fractures. Moreover, patients with vitamin D deficiency have a higher probability of fallings and loss of muscle mass, increasing in turn the risk of fractures. The combined formulation of alendronate and vitamin D as tablets is as effective as the mono-formulation of alendronate, but, furthermore, it has an additional advantage associated with the guaranteed vitamin D intake. At the same time the bioavailability of each component does not differ from the similar index when these agents are used alone.